A graphitization process that can reduce the impurity content of negative electrode materials
Through deionized water washing and repeated demagnetization treatment combined with high-temperature graphitization technology, the problem of high impurity content of the negative electrode material is solved, the conductive performance and safety are significantly improved, and an efficient lithium ion embedded structure is formed.
Patent Information
- Application Number
- CN202310155103.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-23
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-02-23
AI Technical Summary
The prior art has shortcomings in reducing the magnetic impurity content of the negative electrode material of lithium-ion battery, resulting in reduced conductivity and safety hazards, and it is difficult to effectively remove impurities during the preparation process.
Deionized water is used to wash the negative electrode active material, and a regular granular carbon material is formed by grinding, and binder and additives are added in the suspension stage. Repeat magnetic demagnetization with a screening device, combined with high-temperature graphitization to form ordered graphite Crystal structure to improve conductivity.
The magnetic impurity content in the negative electrode material is significantly reduced, the conductivity and battery safety are improved, the lithium ions are embedded in a small depth and short stroke, and the specific surface area is increased to improve the capacity and performance of the battery.
Smart Images

Figure CN116199215B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of negative electrode materials, and in particular to a graphitization process capable of reducing the impurity content of negative electrode materials. Background Art
[0002] The advantages of lithium-ion batteries are large capacity and strong charge retention ability. The negative electrode active material of lithium-ion batteries is carbon material, and the carbon negative electrode replaces the lithium negative electrode. Therefore, the deposition and dissolution of lithium on the negative electrode surface during charging and discharging is changed to the embedding and extraction of lithium in carbon particles, which reduces the possibility of lithium dendrite formation and greatly improves the safety of the battery.
[0003] For example, CN111348646A relates to a preparation method for reducing the graphitization cost of graphite negative electrode materials, comprising the following steps: mixing a polymer material with water, heating, and preparing an adhesive; mixing the raw material powder for preparing the graphite negative electrode material with the adhesive, kneading, and obtaining a mixed material; pressing the mixed material to obtain a pressed product; drying the pressed product; and subjecting the dried material to high-temperature graphitization. In this preparation method, a polymer material that does not contain a benzene ring and is soluble in water is used as an adhesive to press the powder into a block, which greatly increases the density, increases the loading amount of the crucible by 50-80%, and greatly reduces the graphitization cost. In addition, by pressing, the dust in the working environment can be significantly reduced, and the production environment can be improved. However, magnetic impurities such as Fe, Zn, etc. are inevitably mixed in the preparation process of the negative electrode material. The magnetic impurities will increase the self-discharge of the battery, and even cause a short circuit when the magnetic impurity content is high. In addition, the preparation method does not specifically reduce the impurity content of the negative electrode material, resulting in a decrease in the conductivity of the prepared negative electrode material.
[0004] In order to ensure the conductive properties of the negative electrode material, impurities are treated during the preparation process, and a graphitization process is proposed to reduce the impurity content of the negative electrode material. Summary of the invention
[0005] The object of the present invention is to provide a graphitization process that can reduce the impurity content of negative electrode materials, so as to solve the problems raised in the above background technology.
[0006] To achieve the above object, the present invention provides a graphitization process for reducing the impurity content of negative electrode materials, comprising the following steps:
[0007] S1. Washing the negative electrode active material with deionized water, and grinding the negative electrode active material to produce a regular granular carbon material;
[0008] S2, adding a binder, an additive and deionized water to the carbon material in sequence and stirring to produce a negative electrode suspension;
[0009] S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated and dehydrated to form a slurry;
[0010] S4, placing the slurry in a crucible and transferring the crucible to a graphitization furnace chamber for high-temperature graphitization, then cooling and taking out the crucible to complete the graphitization of the negative electrode material.
[0011] As a further improvement of the technical solution, in S1, the negative electrode active material includes carbon nanotubes and soft carbon.
[0012] As a further improvement of the present technical solution, in S1, the grinding method is air flow grinding method.
[0013] As a further improvement of the present technical solution, in S2, the adhesive is carboxymethyl cellulose and styrene-butadiene rubber latex.
[0014] As a further improvement of the present technical solution, in S2, the additive is a boron-containing additive.
[0015] As a further improvement of the technical solution, in S2, the stirring speed after adding deionized water is 40-60 rpm / min.
[0016] As a further improvement of the present technical solution, in S3, the screening device includes a screening part, a vibrator is connected above the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw materials without magnetic material directly flow out from the forked bucket to the finished product outlet.
[0017] As a further improvement of the technical solution, in S3, the negative electrode suspension is demagnetized 3-8 times.
[0018] As a further improvement of the technical solution, in S4, the temperature during graphitization is 2300-2800°C.
[0019] As a further improvement of the technical solution, in S4, the temperature of the crucible when it is taken out is 120-170°C.
[0020] In the present invention, by adding a binder with low metal ion impurity content such as carboxymethyl cellulose and styrene-butadiene rubber emulsion, the bonding of materials can be achieved while minimizing the infiltration of impurities. When the negative electrode material is in the suspension stage, it is repeatedly passed through a screening device, and magnetic substances such as Fe in the suspension are screened out by the screening device, thereby greatly reducing the content of impurities in the negative electrode material and avoiding the conductivity of the negative electrode material being affected. In addition, carbon nanometers and soft carbon are used as carbon sources for the negative electrode material, and the carbon with an amorphous chaotic layer structure is converted into an ordered graphite crystalline structure through high-temperature graphitization, so that when the negative electrode material is used as an electrode, its specific surface area is large, a large amount of lithium ions can be received, and the embedding depth of lithium ions is small and the stroke is short, thereby having good conductivity.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] In the graphitization process that can reduce the impurity content of the negative electrode material, by adding a binder with low metal ion impurity content, the bonding of the materials can be achieved while minimizing the infiltration of impurities. When the negative electrode material is in a suspension stage, it is repeatedly passed through a screening device to screen out magnetic substances, which can reduce the impurity content in the negative electrode material and avoid affecting the conductivity of the negative electrode material. In addition, carbon nanometers and soft carbon are used as carbon sources for the negative electrode material, and are converted into an ordered graphite crystalline structure through high-temperature graphitization, so that the negative electrode material has a large specific surface area when used as an electrode, can receive a large amount of lithium ions, and has a small embedding depth and a short stroke of lithium ions, thereby having good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a flow chart of the present invention. DETAILED DESCRIPTION
[0024] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] See also Figure 1 As shown, the object of the present invention is to provide a graphitization process that can reduce the impurity content of negative electrode materials, comprising the following steps:
[0026] S1. Wash the negative electrode active material with deionized water, grind the negative electrode active material to produce regular granular carbon material, wherein the negative electrode active material includes carbon nanotubes and soft carbon. The SP2 hybrid structure and high aspect ratio of the carbon nanotubes make the embedding depth of lithium ions small, the travel short and the embedding positions multiply, so that it has good electron conduction and ion transport capabilities, and has good electrical conductivity. The soft carbon is easy to graphitize at high temperature and has good compatibility with the electrolyte, and has excellent low-temperature performance, and can assist carbon nanotubes as a component of the negative electrode material. The grinding method is air flow milling method, which utilizes the self-grinding effect of the material, and the high-speed airflow or hot steam generated by compressed air is used to impact the material, so that the materials collide and rub strongly with each other to achieve the purpose of fine crushing. By grinding the negative electrode active material into fine particles, the specific surface area can be increased, so that the channels for lithium ion migration are more, the paths are shorter and the rate performance is better;
[0027] S2. Adding a binder, an additive and deionized water to the carbon material in sequence and stirring at a speed of 40-60 rpm / min to produce a negative electrode suspension, wherein the binder is carboxymethyl cellulose and styrene-butadiene rubber emulsion, and stirring can accelerate the mixing of the various material components to produce a negative electrode suspension, carboxymethyl cellulose can bond the material, provide stable viscosity and adhesion, and has a low content of metal ion impurities. Carboxymethyl cellulose and styrene-butadiene rubber emulsion are mixed and added to increase the viscosity of the negative electrode suspension and prevent precipitation, and have a uniform dispersion effect on the carbon material. The additive is a boron-containing additive, and boride can be produced by adding the boron-containing additive. During the battery cycle, the boride will form a protective film on the surface of the negative electrode, stabilize the interface between the negative electrode and the electrolyte, and ensure the conductive performance;
[0028] S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated and dehydrated to form a slurry, the screening device includes a screening part, a vibrator is connected above the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw material without magnetic material flows directly from the fork bucket to the finished product port, the negative electrode suspension is passed through the screening device, which can effectively reduce the amount of magnetic substances such as Fe in the negative electrode suspension, thereby reducing the impurity content, and the number of demagnetization treatments of the negative electrode suspension is 3-8 times, by repeatedly performing the demagnetization treatment, the content of magnetic impurities in the subsequent slurry can be reduced to the greatest extent, ensuring the conductivity of the manufactured negative electrode material;
[0029] S4. Place the slurry in a crucible and transfer the crucible to the graphitization furnace cavity for high-temperature graphitization, then cool down and take out the crucible to complete the graphitization of the negative electrode material. The temperature during graphitization is 2300-2800°C. High-temperature graphitization can transform amorphous chaotic layered carbon into an ordered graphite crystalline structure. The energy for graphite crystalline structure transformation and atomic rearrangement comes from high-temperature heat treatment. As the heat treatment temperature increases, the graphite layer spacing gradually decreases until the entire graphitization process is completed. The temperature when the crucible is taken out is 120-170°C. When the crucible is taken out, if the temperature is too high, it will lead to oxidation of the negative electrode material, increase the specific surface area, and increase the cost of crucible oxidation damage. When the temperature is too low, the negative electrode powder material will also be oxidized, and the specific surface area will increase.
[0030] In the present invention, by adding a binder with low metal ion impurity content such as carboxymethyl cellulose and styrene-butadiene rubber emulsion, the bonding of materials can be achieved while minimizing the infiltration of impurities. When the negative electrode material is in the suspension stage, it is repeatedly passed through a screening device, and magnetic substances such as Fe in the suspension are screened out by the screening device, thereby greatly reducing the content of impurities in the negative electrode material and avoiding the conductivity of the negative electrode material being affected. In addition, carbon nanometers and soft carbon are used as carbon sources for the negative electrode material, and the carbon with an amorphous chaotic layer structure is converted into an ordered graphite crystalline structure through high-temperature graphitization, so that when the negative electrode material is used as an electrode, its specific surface area is large, a large amount of lithium ions can be received, and the embedding depth of lithium ions is small and the stroke is short, thereby having good conductivity.
[0031] According to the differences in process parameters during the processing, the graphitization process provided by the present invention for reducing the impurity content of the negative electrode material is further described through the following specific embodiments.
[0032] Example 1
[0033] S1. Washing the negative electrode active material with deionized water, grinding the negative electrode active material to produce a regular granular carbon material, wherein the negative electrode active material includes carbon nanotubes and soft carbon, and the grinding method is a jet milling method;
[0034] S2, adding a binder, an additive and deionized water to the carbon material in sequence and stirring at a speed of 40 rpm / min to produce a negative electrode suspension, wherein the binder is carboxymethyl cellulose and styrene-butadiene rubber latex;
[0035] S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated and dehydrated to form a slurry, the screening device includes a screening part, a vibrator is connected to the top of the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw material without magnetic material flows directly from the fork bucket to the finished product outlet, and the number of demagnetization treatments of the negative electrode suspension is 3 times;
[0036] S4. Placing the slurry in a crucible and transferring the crucible to a graphitization furnace cavity for high-temperature graphitization, cooling the crucible and taking it out to complete graphitization of the negative electrode material, wherein the temperature during graphitization is 2300° C., and the temperature when the crucible is taken out is 120° C.
[0037] Example 2
[0038] S1. Washing the negative electrode active material with deionized water, grinding the negative electrode active material to produce a regular granular carbon material, wherein the negative electrode active material includes carbon nanotubes and soft carbon, and the grinding method is a jet milling method;
[0039] S2, adding a binder, an additive and deionized water to the carbon material in sequence and stirring at a speed of 50 rpm / min to produce a negative electrode suspension, wherein the binder is carboxymethyl cellulose and styrene-butadiene rubber latex;
[0040] S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated to remove water to form a slurry, the screening device includes a screening part, a vibrator is connected to the top of the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw material without magnetic material flows directly from the fork bucket to the finished product outlet, and the number of demagnetization treatments of the negative electrode suspension is 5 times;
[0041] S4. Placing the slurry in a crucible and transferring the crucible to a graphitization furnace chamber for high-temperature graphitization, cooling the crucible and taking it out to complete graphitization of the negative electrode material, wherein the temperature during graphitization is 2600° C., and the temperature when the crucible is taken out is 150° C.
[0042] Example 3
[0043] S1. Washing the negative electrode active material with deionized water, grinding the negative electrode active material to produce a regular granular carbon material, wherein the negative electrode active material includes carbon nanotubes and soft carbon, and the grinding method is a jet milling method;
[0044] S2, adding a binder, an additive and deionized water to the carbon material in sequence and stirring at a speed of 60 rpm / min to produce a negative electrode suspension, wherein the binder is carboxymethyl cellulose and styrene-butadiene rubber latex;
[0045] S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated and dehydrated to form a slurry, the screening device includes a screening part, a vibrator is connected to the top of the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw material without magnetic material flows directly from the fork bucket to the finished product outlet, and the number of demagnetization treatments of the negative electrode suspension is 8 times;
[0046] S4. Placing the slurry in a crucible and transferring the crucible to a graphitization furnace chamber for high-temperature graphitization, cooling the crucible and taking it out to complete graphitization of the negative electrode material, wherein the temperature during graphitization is 2800° C., and the temperature when the crucible is taken out is 170° C.
[0047] Example 4
[0048] S1. Washing the negative electrode active material with deionized water, grinding the negative electrode active material to produce a regular granular carbon material, wherein the negative electrode active material includes carbon nanotubes and soft carbon, and the grinding method is a jet milling method;
[0049] S2, adding a binder, an additive and deionized water to the carbon material in sequence and stirring at a speed of 45 rpm / min to produce a negative electrode suspension, wherein the binder is carboxymethyl cellulose and styrene-butadiene rubber latex;
[0050] S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated and dehydrated to form a slurry, the screening device includes a screening part, a vibrator is connected to the top of the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw material without magnetic material flows directly from the fork bucket to the finished product outlet, and the number of demagnetization treatments of the negative electrode suspension is 8 times;
[0051] S4. Placing the slurry in a crucible and transferring the crucible to a graphitization furnace cavity for high-temperature graphitization, cooling the crucible and taking it out to complete graphitization of the negative electrode material, wherein the temperature during graphitization is 2500° C., and the temperature when the crucible is taken out is 150° C.
[0052] Table 1 Comparison of process parameters in Examples 1-4
[0053]
[0054] Comparative Example 1
[0055] This comparative example adopts the processing technology of Example 1, and the stirring speed is set to 30 rpm / min, and the rest remains unchanged. The specific steps are similar to those of Example 1, and will not be repeated in this comparative example.
[0056] Comparative Example 2
[0057] This comparative example adopts the processing technology of Example 2, and the stirring speed is set to 55 rpm / min, and the rest remains unchanged. The specific steps are similar to those of Example 2, and will not be repeated in this comparative example.
[0058] Table 2 Comparison of process parameters in comparative examples 1-2
[0059]
[0060] Comparative Example 3
[0061] This comparative example adopts the processing technology of Example 3, sets the number of demagnetization processes to 2, and keeps the rest unchanged. The specific steps are similar to those of Example 3, and will not be described in detail in this comparative example.
[0062] Comparative Example 4
[0063] This comparative example adopts the processing technology of Example 4, and the number of demagnetization processes is set to 10 times, while the rest remains unchanged. The specific steps are similar to those of Example 4, and will not be repeated in this comparative example.
[0064] Table 3 Comparison of process parameters in comparative examples 3-4
[0065]
[0066] Comparative Example 5
[0067] This comparative example adopts the processing technology of Example 1, and the graphitization temperature is set to 2000° C., and the rest remains unchanged. The specific steps are similar to those of Example 1, and will not be repeated in this comparative example.
[0068] Comparative Example 6
[0069] This comparative example adopts the processing technology of Example 2, and the graphitization temperature is set to 3000° C., and the rest remains unchanged. The specific steps are similar to those of Example 2, and will not be repeated in this comparative example.
[0070] Table 4 Comparison of process parameters in comparative examples 5-6
[0071]
[0072] Comparative Example 7
[0073] This comparative example adopts the processing technology of Example 3, sets the removal temperature to 100° C., and keeps the rest unchanged. The specific steps are similar to those of Example 3, and will not be described in detail in this comparative example.
[0074] Comparative Example 8
[0075] This comparative example adopts the processing technology of Example 4, setting the removal temperature to 180° C. and keeping the rest unchanged. The specific steps are similar to those of Example 4 and will not be described in detail in this comparative example.
[0076] Table 5 Comparison of process parameters in comparative examples 7-8
[0077]
[0078] Test example
[0079] The negative electrode material was prepared according to a graphitization process for reducing the impurity content of the negative electrode material provided in Examples 1-4 and Comparative Examples 1-8, and the magnetic substance content in the prepared negative electrode material was tested according to GB / T 33827-2017 "Determination of the content of magnetic substance in nano-negative electrode materials for lithium batteries", and the test values were filled in Table 6.
[0080] Table 6 Comparison of magnetic impurity content of negative electrode materials prepared in Example and Comparative Example
[0081] Magnetic impurity content / PPM Example 1 0.10 Example 2 0.08 Example 3 0.11 Example 4 0.09 Comparative Example 1 0.14 Comparative Example 2 0.13 Comparative Example 3 0.16 Comparative Example 4 0.13 Comparative Example 5 0.15 Comparative Example 6 0.13 Comparative Example 7 0.15 Comparative Example 8 0.16
[0082] According to Table 6, by comparing the graphitization process for reducing the impurity content of the negative electrode material provided by Examples 1-4 with the graphitization process for reducing the impurity content of the negative electrode material provided by Comparative Examples 1-8, the magnetic impurity content of the negative electrode material processed by the embodiment process is lower than that of the negative electrode material processed by the comparative example process, and the magnetic impurity content of the negative electrode material processed by the embodiment process is lower than 0.11 PPM, while the magnetic impurity content of the negative electrode material processed by the comparative example process with different process parameters is increased. Therefore, the graphitization process for reducing the impurity content of the negative electrode material provided by the present invention can prepare a negative electrode material with a low magnetic impurity content.
[0083] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not intended to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A graphitization process for reducing the impurity content of negative electrode materials, characterized in that: The following steps are involved: S1. Washing the negative electrode active material with deionized water, grinding the negative electrode active material to produce a regular granular carbon material, wherein the negative electrode active material includes carbon nanotubes and soft carbon, and the grinding method is a jet milling method; S2, adding a binder, an additive and deionized water to the carbon material in sequence and stirring at a speed of 50 rpm / min to produce a negative electrode suspension, wherein the binder is carboxymethyl cellulose and styrene-butadiene rubber latex; S3, after the negative electrode suspension is demagnetized by a screening device to remove magnetic substances, it is heated to remove water to form a slurry, the screening device includes a screening part, a vibrator is connected to the top of the screening part, the vibrator can evenly disperse the material into the cavity, a medium net is arranged in the cavity, the medium net is connected to a vibration motor that drives the mesh plate to rotate, when the material enters the cavity, the medium net is magnetized to absorb the magnetic material, and the raw material without magnetic material flows directly from the fork bucket to the finished product outlet, and the number of demagnetization treatments of the negative electrode suspension is 5 times; S4, placing the slurry in a crucible and transferring the crucible to a graphitization furnace chamber for high-temperature graphitization, then cooling and taking out the crucible to complete graphitization of the negative electrode material, wherein the temperature during graphitization is 2600° C., and the temperature when the crucible is taken out is 150° C.; The magnetic impurity content of the prepared negative electrode material is 0.08PPM.
